Study on the Mechanism of Sancao Tiaowei Decoction in the Treatment of MNNG-Induced Precancerous Lesions of Gastric Carcinoma Through Hedgehog Signaling Pathway - Chae, Yeon (Frontiers in Oncology, 2022)
Sancao Tiaowei Decoction (SCTWD), a traditional Chinese medicine created by Professor Chen Weijian, has been used in the prevention and treatment of precancerous lesions of gastric carcinoma (PLGC). However, its mechanism has not been made clear. This study aimed to evaluate the therapeutic effect of SCTWD on 1-methyl-3-nitro-1-nitrosoguanidine-induced PLGC in rats and the mechanism of this effect. We found that SCTWD effectively repaired gastric mucosal injury, reversed the process of PLGC, and inhibited the occurrence of gastric cancer to some extent. In the results of hematoxylin-eosin (HE) staining, the number and arrangement of mucosal glands and the number of mononuclear cells in the lamina propria were improved in varying degrees; the enzyme-linked immunosorbent assay (ELISA) showed that the PG I and PGR of the medication treatment group were significantly higher; a Reverse Transcription-Polymerase Chain Reaction (RT-PCR) test showed that SCTWD could significantly upregulate the expression levels of Shh, Ptch, and Gli-1 in the gastric tissue of rats. The immunohistochemical method showed that SCTWD could significantly upregulate the protein expressions of Shh, Gli-1, Smo, cyclin D1, CDKN2A/p16INK4a, and NF-κBP65 and could reduce the expression of Ptch at the same time. Through the preliminary analysis of 75 compounds screened by UPLC-Q-TOF-MS, the main components, such as organic acids, esters and anhydrides, flavonoids, phenols, tanshinones, and so on, have anti-inflammatory and anti-tumor pharmacological effects. The results of KEGG enrichment analysis showed that 5 signaling pathways related to this project were found, and 33 differential genes were presented to construct the interaction network. These results suggested that SCTWD had a good regulatory effect on PLGC and thus may have a multi-targeted effect; SCTWD can not only significantly improve the pathological changes of gastric mucosa in rats with PLGC but also exert a strong effect of the regulation of the hedgehog signaling pathway.